Role of quantitative hepatitis B surface antibodies in preventing hepatitis B virus-related hepatitis in patients treated with rituximab. Issue 12 (15th October 2021) - Pei, Sung-Nan; Liu, Yan-Fang; Kuo, Chin-Yuan; Wang, Ming-Chung; Ma, Ming-Chun; Liao, Chun-Kai; Ng, Hwee-Yeong; Chen, Chien-Hung
Abstract: Hepatitis B virus (HBV) reactivation is a well-known complication after rituximab-based chemotherapy in patients with B cell lymphoma (BCL) who have resolved HBV infection. This retrospective cohort study used electronic medical records from the Kaohsiung Chang Gung Memorial Hospital. There were 128 patients with BCL and resolved HBV infection treated with 1st-line rituximab-containing therapy from 2008 to 2013. No patient received antiviral prophylaxis. Patients with high pretreatment hepatitis B surface antibody (anti-HBs titer ≥100 mIU/mL), had significantly less HBV reactivation (2.0%, 1/49) than patients with low (10–100 mIU/mL, 10.8%, 4/37) or negative anti-HBs (<10 mIU/mL, 23.8%, 10/42) ( p = 0.001). No patient in the high group vs. 1 (2.7%) low group vs. 6 (14.3%) negative group developed HBV-related hepatitis ( p = 0.002). Patients with high pretreatment anti-HBs have a low risk of HBV-related complications and may not require antiviral prophylaxis. We propose an algorithm for the management of HBV reactivation risk in BCL.